Auditor Quality and Discretionary Accruals: Case of Australian Listed Companies - Rusmin Rusmin (Jurnal Akuntansi dan Auditing Indonesia, 2010)
This study empirically examines the relation between two dimensions of auditor quality: auditor independence and auditor specialization, and the level of discretionary accruals, a proxy for earnings management. This study focuses on earnings management in response to mounting pressure amongst investors, policy makers and corporate governance reformists for mechanism to curb excessive opportunistic behaviour amongst corporate management. Auditor independence and auditor specialization are the epicentre of this analysis as these two factors are considered to be key determinants of earnings management. As earnings management, auditor independence and auditor specialization are unobservable, I use absolute discretionary accruals, the ratio of non-audit to total fees and auditor industry market share as respective proxies. Using 2004 data hand collected from 325 Australian publicly listed firms I find no sig-nificant association between the non-audit/total fee ratio and the magnitude of earnings man-agement. Thus, this result suggests the provision of non-audit services by the incumbent auditor does not compromise independence and, therefore, the auditor’s ability to constrain earnings management. This study also fail to find a firm engaging an audit firm with industry specializa-tion skills has significantly lower levels of absolute discretionary accruals than a firm using the services of a non-specialist. The main findings of this study are robust to various sensitivity checks. Findings have implications for various stakeholders. For instance, there is currently ap-pears to be a preoccupation amongst corporate governance reformists and policy makers inter-nationally to curb the provision of non-audit services by the incumbent auditor to aid in such matters as the reduction in earnings management. These findings suggest this preoccupation may be misplaced and that constraining the ability of firms purchase non-audit services from the in-cumbent auditor could provide only limited benefits whilst increasing costs. In addition, policy makers and reformists need to consider more clearly the costs and benefits of any moves to limit industry concentrations within the audit market.Keywords:    auditor independence, earnings management, auditor specialization